Investigation of Antioxidant Properties of Three Naturally Isolated Microalgae: Identification and Bioinformatics Evaluation of the Most Efficient Strain - Morowvat, Mohammad H.; Goharian, Sara; Ghasemi, Younes (Recent Patents on Biotechnology, 2019)
Background and Objectives: In this study, three naturally isolated species of microalgae were investigated for their antioxidant activity using DPPH assay and polyphenol contents through Folin-ciocalteu analysis. Methods: Three different solvents including hexane, ethyl acetate and water, which present different polarities were utilized to extract the bioactive components from three different microalgal strains. Results: The investigated species exhibited considerable amounts of antioxidants (25.88 ± 0.48 μmol Trolox g-1 in Scenedesmus obliquus) and polyphenol compounds (27.14 ± 0.40 mg GAE g-1 in Chlorella vulgaris). The observed correlation coefficient (R2=0.8265) between the two studied parameters confirmed the great contribution of the phenolic compounds in the observed antioxidant activities. Conclusion: The phylogenetics and other bioinformatic tools were confirmed as a useful method for identification of the most prominent species. The obtained data and patents warrant the potentials of naturally isolated microalgal strains for obtaining different antioxidant and polyphenolic bioactive compounds.
Keywords: folinciocalteu analysis